An intricate pulmonary infection in a patient with T-cell Acute Lymphoblastic Leukemia - Calogero Vetro; Laura Trovato; Valeria Calafiore; Alessandra Romano; Rosario Cunsolo; Giorgio Giulietti; Salvatore Oliveri; Francesco Di Raimondo (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Non-albicans Candida (NAC) is rarely isolated from specimens. Here, we report a case of pulmonary infiltrates strongly suspected for Candida guilliermondii infection in a patient affected by T-cell Acute Lymphoblastic Leukemia (T-ALL) resistant to chemotherapy.